Projekt CRISP - prispevek k merjenju subjektivnega doživljanja otrokovih pravic in kakovosti življenja - Pavlović, Zoran (Šolsko polje, 2007)
The purpose of this paper is to present selected findings from the second sweep of the CRISP study (Children's Rights International Study Project). The paper presents some of the international comparisons and selected findings gathered in Slovenia since 1991. In the following paper the potentials of the design to serve longitudinal comparisons about the issue of children's rights and children's quality of life inside a given country are also pointed out.
Keywords: mednarodne študije; otrokove pravice; projekti; vzgoja in izobraževanje